Malaysia’s law in dealing with human trafficking: has it been enough to protect the victim? - Ab Hamid, Zuraini (2023)
There is no region that is exempt from the organised crime of human trafficking. Although the United States of America (USA) has been listed in Tier 1 of the TIP report since its inception, the country has never been exempted from this heinous crime as the nature of the crime itself involve the characteristics of transnational organised crime. To be ranked at Tier 1 in the Trafficking in Persons Report (TIP), states parties must meet the minimum standards for combating trafficking in persons under Section 108 of the Trafficking Victims Protection Reauthorization Act 2000 (TVPA). The requirement is to has impeccable law that provide severe punishment to the traffickers. Using a qualitative research method, this paper will examine whether the laws in Malaysia are sufficient to protect victims of trafficking. It is found that Malaysia has an impeccable law. Unfortunately, since 2001, Malaysia fails to be in Tier 1 of the TIP report because it is inefficient in some areas and its ability to protect victims is questionable.